2011
DOI: 10.1016/j.devcel.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Checkpoint Silencing Requires Association of PP1 to Both Spc7 and Kinesin-8 Motors

Abstract: The spindle checkpoint is the prime cell-cycle control mechanism that ensures sister chromatids are bioriented before anaphase takes place. Aurora B kinase, the catalytic subunit of the chromosome passenger complex, both destabilizes kinetochore attachments that do not generate tension and simultaneously maintains the spindle checkpoint signal. However, it is unclear how the checkpoint is silenced following chromosome biorientation. We demonstrate that association of type 1 phosphatase (PP1(Dis2)) with both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
224
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(235 citation statements)
references
References 47 publications
10
224
0
1
Order By: Relevance
“…Metaphase plate thinning occurs as cells progress towards anaphase implicating the existence of a phosphatase that counteracts Cdk1 phosphorylation of Kif18A. Previous studies revealed that Klp5/Klp6, the fission yeast Kinesin-8, contain a conserved motif (R/KxVxF/W; x denoting any aa) that mediates binding to protein phosphatase-1 (PP1) 25 . To test the idea that PP1 is the phosphatase that antagonizes Cdk1, we first analysed if Kif18A interacts with PP1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaphase plate thinning occurs as cells progress towards anaphase implicating the existence of a phosphatase that counteracts Cdk1 phosphorylation of Kif18A. Previous studies revealed that Klp5/Klp6, the fission yeast Kinesin-8, contain a conserved motif (R/KxVxF/W; x denoting any aa) that mediates binding to protein phosphatase-1 (PP1) 25 . To test the idea that PP1 is the phosphatase that antagonizes Cdk1, we first analysed if Kif18A interacts with PP1.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, an interaction between Kinesin-8 and PP1 has been recently reported for fission yeast Klp5/Klp6 and this interaction has been shown to be essential for timely SAC silencing 25 . Our data revealed that the expression of Kif18A deficient in PP1 binding (GFP-Kif18A PP1D ) as well causes a delay in anaphase onset (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we draw a parallel to dis2/PP1, a gene that displays similar cell cycle phenotypes to dis3 in S. pombe and flies (Ohkura et al 1988;Axton et al 1990). During mitosis, Dis2/PP1 activity is thought to prevent chromosome separation until all chromosome pairs are bioriented on the mitotic spindle (Vanoosthuyse and Hardwick 2009;Meadows et al, 2011); once this criterion is met, its activity is thought to be directly Figure 7 dis3 and ras cooperate to accelerate cells through the G2/M phase. Graph shows the relative percentage of cells of the indicated genotype in the G1, S, and G2/M phases of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cells expressing a motor defective Klp5-Klp6 complex display all of these phenotypes, indicating that motor activity is important for kinesin-8 function. However it has been shown recently that the non-motor tail domains of Klp5 and Klp6 bind to type 1 phosphatase (PP1) and that this pool of PP1 helps to regulate both mitotic microtubule mechanics and efficiently silence the spindle checkpoint (Meadows et al 2011 …”
Section: Association To Type-1-phosphatase (Pp1)mentioning
confidence: 99%